The Effect of Brand Image and Service Quality on The Decision to Choose With Word of Mouth as Mediation Variable at Prof. Dr. Tabrani Hospital Pekanbaru - Agustin, Ririn; Hendriani, Susi; Syapsan, Syapsan (Program Pascasarjana, Universitas Riau, 2020)
This study is aimed to examine the effect of brand image and service quality on patient decision with word of mouth as mediation variable. The study was conducted in Prof. Dr. Tabrani Hospital in Pekanbaru. The data used consist of primary and secondary data. Data were collected by using questionnaires that given to 120 patients of Prof. Dr. Tabrani Hospital in Pekanbaru that used purposive sampling. Descriptive analysis method is used to describe the characteristics of respondents and the research hypotheses by using relevant statistical tests. Variables used are brand image and service quality as independent variable, patient decision as dependent variable and word of mouth as mediation variable. Analyzer used is path analysis by using program of SPSS 21 for windows. The results of this study are found that brand image and service quality have a direct influence significantly and positive on word of mouth, brand image and service quality have a direct influence significantly and positive on patient decision. Indirectly, word of mouth has a positive mediation role on the influence of brand image on patient decision and word of mouth has a positive mediation role on the influence of service quality on patient decision. The improvement of brand image and service quality are recommended in order to optimize patient decision.